Decision Support Approach for Managers in the Application of the CSR Concept - Nora Rodek Berkes (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
In today's globalized world we hear more and more about sustainable development, ethical corporate governance, ecological footprint and similar concepts that are inspiring us to behave and operate responsibly from individuals to large enterprises. Previous researches on the subject have highlighted the fact that most of the company executives are not aware of the elements of the CSR concept (Corporate Social Responsibility) and they identify CSR as environmental protection and charity. A directive of CSR is needed which enables companies to learn about the concept of CSR and its elements, so this information could help them in responsible decision making. During the research the CSR excellence management and assessment tool (CSR EMAT) was developed based on the logic of the EFQM Excellence Model. It serves as a guideline and evaluation system for companies and makes them comparable as a result of the evaluation process. Companies can be divided into different groups according to their CSR excellence as it is supported by the examples in the study.
Keywords: M14; 330; Corporate Social Responsibility; sustainability; management; EFQM Excellence Model; CSR EMAT; CSR excellence management and assessment tool